Obesitas dan Depresi pada Orang Dewasa - Nyoman Mupu Murtane (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; obesity is the most common chronic physical disease in modern society, and depression is the most common psychological condition. Destination; see if there is a significant relationship between obesity and depression. Method; a literature review study, in which researchers seek, combine the essence, and analyze facts from several scientific sources that are accurate and valid, which support and become evidence. Result; that depression and obesity are both associated with social stigma, feelings of low self-esteem, and chronic health conditions. When depression and obesity co-exist, the adverse health and social consequences are significant. Conclusion; Depression is a mood disorder characterized by the main symptoms of depressive effects, loss of interest and anhedonia, and loss of energy which is characterized by rapid fatigue